La conservación del bosque en Tetela del Volcan, Morelos, vista a través de un análisis situacional - Chávez-Cortés, Juan Manuel; Ramírez Granados, Gabriela; Medina, Marisol (Instituto de Ecología, A.C., 2016)
Multi-stakeholders involvement in forest ecosystems management is considered as one of the main pillars in Sustainable Forest Management (SFM). However, it is also seen as the “weak pillar” because of the required collaboration of multiple-stakeholders. In order to obtain this collaboration, the planner has to understand the perceptions and the ways different stakeholders influence forest management. He also has to identify the problems and conflicts related to this management. This paper states that a searching for alternatives to face problems related to the achievement of SFM requires situational (context) analysis of the stakeholders involved in forest management. In addition, a case study as research strategy is employed for testing this postulate. For this reason, the factors that foster and restrict a forest conservation project for SFM planning purposes in the municipality of Tetela del Volcán, Morelos, México, are analyzed and employed. The authors identified “the lack of a valuing culture of forest resources” as the main problem to achieve MFS. In order to tackle this complex problem, two strategic actions programs are built. One related to improve the budget for forest conservation and restoration, and other to empower the communication, coordination and negotiation of the stakeholders of the municipality.